Does Margin Length Predict Recurrence After Partial Nephrectomy, or Is Presence Alone Sufficient? (Journal of Kidney Cancer, 2026)
To evaluate whether the length of positive surgical margin carries a risk for recurrence, data of patients that underwent partial nephrectomy (PN) from six centers were evaluated. Fifty-three patints with positive surgical margins (PSMs) (the PSM group) and 438 patients with negative surgical margin (the NSM group) were included in the present study. Pathologic reevaluations were performed, and surgical margins were measured in micrometers. The number of positive margin areas, and the length of the maximum and total positive margins were evaluated. Data were analyzed using SPSS 27 package program. A p-value less than 0.001 was considered statistically significant. Local recurrence occured in 16.98% of patients in the PSM group and 4.24% of patients in the NSM group. (p0.01). However, positive surgical margin was an important risk factor for local recurrence (p